The Intensification of Time: Michael Wyschogrod and the Task of Christian Theology - Lowe, Walter (Modern theology, 2006)
In conversation with Karl Barth, Michael Wyschogrod observes that with God's promises, unlike humans', "if we have [God's] promise, we have its fulfillment". The essay considers Wyschogrod's implicit intensification of time, which displaces common linear views of time. Wyschogrod charges that Christian understandings of fulfillment imply a completed line of history which is all too luminous. Edwyn Hoskyns's study of John's Gospel suggests an alternative; namely, a Christian intensification of time which finds in Jesus both life and judgment, love and condemnation. Such realized apocalyptic, as it were, confronts readers with a density or relative darkness more consonant with Hebrew scriptural revelation.